Assessment of Nutrient Sufficiency Through Body Condition Score: A Study Case at The Ongole Cross-Breed Cattle Breeding Center, Kebumen, Central Java - Negoro, Putut Suryo; Purba, Riris Delima; Gopar, Ruslan Abdul; Negara, Windu; Putri, Ezi Masdia; Rofiq, M Nasir; Kumalasari, Nur Rochmah (Buletin Peternakan, 2025)
This study aimed to evaluate the feeding practices and nutritional intake of Ongole crossbred (PO) cattle in Kebumen, Central Java. This study focused on body condition scores (BCSs) and their implications for cattle performance. The parameters observed in this study included the feed composition, nutrient content, and impact of different BCSs on nutrient intake. The results of this research revealed that PO cattle with poor BCS did not receive sufficient feed, resulting in suboptimal nutrient intake. Moreover, those with medium BCS receive sufficient feed but still lack protein intake. In contrast, PO cattle with optimum BCS demonstrated the higher performance compared to other BCS groups, with crude protein intake of 0.57 kg (8.81%), 0.15 kg of extract (2.32%), 2.08 kg of crude fibre (32.15%), 3.81 kg of neutral detergent fiber 58.89%), 2.27 kg of acid detergent fiber (35.08%), and 4.00 kg of total digestible nutrient (61.82%) of the total dry matter intake, amounting to 6.47 kg. The findings underscore the importance of proper feeding practices tailored to the nutritional needs of cattle to optimize cattle performance